Worsening of parkinsonism after the use of veralipride for treatment of menopause: case report - Helio A. G. Teive; Daniel S. Sa (Arquivos de Neuro-Psiquiatria)
We describe a female patient with stable Parkinson's disease who has shown a marked worsening of her motor functions following therapy of menopause related symptoms with veralipride, as well as the improvement of her symptoms back to baseline after discontinuation of the drug. We emphasize the anti-dopaminergic effect of veralipride.